Job Satisfaction and Employee’s Commitment to the Performance: Case Study of Angkasa Pura I Juanda International Airport - Marsudi Lestariningsih (Innovation Business Management and Accounting Journal, 2022)
This study examined the effect of employee’s job satisfaction, employee’s commitment to the employee’s performance at PT. (Persero) Angkasa Pura I Juanda International Airport. The population consisted of 78 employees as a respondent and using a survey research method with proportional cluster random sampling as a technique to choose the sample size, also simple random sampling to choose the respondent, and using the path analysis tests the hypothesis. The result showed that employee’s job satisfaction has a direct significant and indirectly significant effect on performance through employee’s commitment. Also, an employee’s commitment has a significant direct effect on an employee’s performance.